Serotonin and psilocybin activate 5-HT1B receptors to suppress cortical signaling through the claustrum - Maxwell B. Madden; Chloe Schaefgen; Binita Vedak; Jian Kwon; Kiara S. Dresp Pedra; Samuel H. Sheats; Adam C. Puche; Steffen B. E. Wolff; Brian N. Mathur (Nature Communications)
Abstract Through its widespread reciprocal connections with the cerebral cortex, the claustrum is implicated in sleep and waking cortical network states. Yet, basic knowledge of neuromodulation in this structure is lacking. The claustrum is richly innervated by serotonergic fibers, expresses serotonin receptors, and is suggested to play a role in the ability of psilocybin, which is metabolized to the non-specific serotonin receptor agonist psilocin, to disrupt cortex-wide network states. We therefore addressed the possible role of serotonin, and the classic psychedelic psilocybin, in modulating cortical signaling through the claustrum. We show that serotonin activates 5-HT1B receptors on anterior cingulate cortex inputs – a primary driver of claustrum activity – to suppress signaling to parietal association cortex-projecting claustrum neurons. Additionally, we demonstrate that psilocybin injection also activates anterior cingulate cortex presynaptic 5-HT1B receptors to suppress cortical signaling through the claustrum. Thus, serotonin, via 5-HT1B, may provide gain-control of cortical input to the claustrum, a mechanism that may be directly targeted by psilocybin to modulate downstream cortical network states.